TRAUMA INDUCES INTRAVASCULAR HEMOLYSIS, EXACERBATED BY RED BLOOD CELL TRANSFUSION AND ASSOCIATED WITH DISRUPTED ARGININE–NITRIC OXIDE METABOLISM. Issue 1 (16th January 2023) - Schaid, Terry R.; Cohen, Mitchell J.; D'Alessandro, Angelo; Silliman, Christopher C.; Moore, Ernest E.; Sauaia, Angela; Dzieciatkowska, Monika; Hallas, William; Thielen, Otto; DeBot, Margot; Cralley, Alexis; LaCroix, Ian; et al.
ABSTRACT: Background: Severe injury can provoke systemic processes that lead to organ dysfunction, and hemolysis of both native and transfused red blood cells (RBCs) may contribute. Hemolysis can release erythrocyte proteins, such as hemoglobin and arginase-1, the latter with the potential to disrupt arginine metabolism and limit physiologic NO production. We aimed to quantify hemolysis and arginine metabolism in trauma patients and measure association with injury severity, transfusions, and outcomes. Methods: Blood was collected from injured patients at a level I trauma center enrolled in the COMBAT (Control of Major Bleeding After Trauma) trial. Proteomics and metabolomics were performed on plasma fractions through liquid chromatography coupled with mass spectrometry. Abundances of erythrocyte proteins comprising a hemolytic profile as well as haptoglobin, l -arginine, ornithine, and l -citrulline (NO surrogate marker) were analyzed at different timepoints and correlated with transfusions and adverse outcomes. Results: More critically injured patients, nonsurvivors, and those with longer ventilator requirement had higher levels of hemolysis markers with reduced l -arginine and l -citrulline. In logistic regression, elevated hemolysis markers, reduced l -arginine, and reduced l -citrulline were significantly associated with these adverse outcomes. An increased number of blood transfusions were significantly associated with elevated hemolysis markers and reduced l -arginine and l -citrulline independently of New Injury Severity Score and arterial base excess. Conclusions: Severe injury induces intravascular hemolysis, which may mediate postinjury organ dysfunction. In addition to native RBCs, transfused RBCs can lyse and may exacerbate trauma-induced hemolysis. Arginase-1 released from RBCs may contribute to the depletion of l -arginine and the subsequent reduction in the NO necessary to maintain organ perfusion.